PENERAPAN DMAIC DALAM UPAYA MENURUNKAN DEFECT PADA PROSES GREEN TIRE SERVICE (GTS) SIZE LIGHT TRUCK DI PT XYZ [IMPLEMENTATION OF DMAIC TO REDUCE DEFECTS IN THE GREEN TIRE SERVICE (GTS) PROCESS FOR LIGHT TRUCK SIZES AT PT XYZ] - Rudy Vernando Sialahi; Deotemanta Pasaribu (Universitas Pelita Harapan, 2024)
PT XYZ is a company engaged in the manufacturing industry which produces tires. The problem faced by the company is related to the production process which still produces defective products that exceed the target of the key performance indicators (KPI) set by the company. This research analyzes and applies DMAIC (Define, Measure Analyze, Improve, Control) to improve product quality. With Stage D (Define) to find out the process flow, making SIPOC (Supplier-Input- Process-Output- Customer), and knowing the types of defects in the GTS (green tire service) process. At stage M (Measure), measurements are carried out using a Pareto diagram to determine the type of defect and the machine with the highest level of defect that will need to be repaired. In stage A (Analyze) the cause of the problem is searched using a fishbone diagram. After the cause of the defect is known, stage I (Improve) is carried out. At this stage, the root of the problem that has been found and explained in the analyze stage is repaired. After repairs have been carried out, stage C (Control) is carried out by creating an SOP (Standard Operating Procedure) for using the VTT-1 machine, a checksheet for machine cleanliness, and a checksheet for changing gloves. In this research, it is known that the defect crease on the VTT(Venting)-1 machine with a DPMO value of 40.36 with a sigma level of 5.43 before the application of DMAIC, after the application of DMAIC the defect crease on the VTT-1 machine decreased to 82% with a DPMO value of 7.25 with a level of sigma 5.84.Bahasa Indonesia Abstract:PT XYZ merupakan perusahaan yang bergerak dalam bidang industri manufaktur yang memproduksi ban. Permasalahan yang dihadapi perusahaan adalah terkait proses produksi yang masih membuat produk defect overtarget dari key performance indicator (KPI) yang ditetapkan oleh perusahaan. Penelitian ini melakukan analisis dan penerapan DMAIC untuk memperbaiki kualitas produk. Dengan Tahap D (Define) untuk mengetahui alur proses, Pembuatan SIPOC, dan mengetahui jenis defect pada proses GTS. Pada tahap M (Measure) dilakukan pengukuran dengan diagram pareto untukmengetahui jenis defect dan mesin dengan tingkat kecacatan yang paling tinggi yang nantinya perlu adanya perbaikan. Pada tahap A (Analyze) dilakukan pencarian penyebab masalah dengan menggunakan fishbone diagram. Setelah diketahui penyebab terjadinya defect, dilakukan tahap I (Improve) pada tahap ini dilakukan perbaikan akar masalah yang telah ditemukan dan dijelaskan pada tahap analyze. Setelah dilakukan perbaikan, tahap C (Control) dilakukan dengan membuat SOP penggunaan mesin VTT-1, checksheet kebersihan mesin, dan checksheet pergantian sarung tangan. Pada penelitian ini di ketahui bahwa defect crease padamesin VTT-1 dengan nilai DPMO 40,36 dengan tingkat sigma 5,43 sebelum penerapan DMAIC, setelah penerapan DMAIC defect crease pada mesin VTT-1 turun hingga 82 % dengan nilai DPMO 7,25 dengan tingkat sigma 5,84